2022
DOI: 10.3390/biom12070971
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features and Neuroinflammatory Mechanisms of SARS-CoV-2 in the Brain and Potential Therapeutic Approaches

Abstract: The number of deaths has been increased due to COVID-19 infections and uncertain neurological complications associated with the central nervous system. Post-infections and neurological manifestations in neuronal tissues caused by COVID-19 are still unknown and there is a need to explore how brainstorming promoted congenital impairment, dementia, and Alzheimer’s disease. SARS-CoV-2 neuro-invasion studies in vivo are still rare, despite the fact that other beta-coronaviruses have shown similar properties. Neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 142 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…Of interest is that the regression analysis of the cognitive tests revealed no variables which were consistently and independently associated with cognitive impairments, except poor education level. Since poor education may adversely affect cognition via low cognitive reserves, future studies should be conducted on this specific patient group [ 5 ]. In contrast to the results from Almeria et al [ 40 ], the presence of neurological symptoms was not consistently associated with cognitive functions in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest is that the regression analysis of the cognitive tests revealed no variables which were consistently and independently associated with cognitive impairments, except poor education level. Since poor education may adversely affect cognition via low cognitive reserves, future studies should be conducted on this specific patient group [ 5 ]. In contrast to the results from Almeria et al [ 40 ], the presence of neurological symptoms was not consistently associated with cognitive functions in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms by which SARS-CoV-2 affects the brain may include processes related to inflammation, neuroinvasion, microvascular injury, and hypoxia [ 4 ]. Emerging evidence has revealed that the olfactory bulb, thalamus, and brain stem are infected by the virus through a trans-synaptic transfer [ 5 ]. The excessive release of inflammatory signals such as cytokines and chemokines, and infection of the astrocytes induce neuroinflammation and neuronal death and may result in further neurodegenerative complications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…(b) SARS-CoV-2 can directly invade the brain. The neuro-invasion pathway may involve direct brain damage by SARS-CoV-2 and/or the persistence of the coronavirus activating long-lasting inflammation in the brain to cause depression [ 54 , 55 ]. As previously mentioned, depression and other long COVID neuropsychiatric sequelae may share common pathogenic pathways that involve both systemic inflammation and neuroinflammation.…”
Section: Could the Inflammation Theory Of Depression Apply To Long Co...mentioning
confidence: 99%
“…Najafloo et al (2021) examined the mechanisms associated with olfactory impairment in neocoronary pneumonia, including olfactory cleft syndrome, local inflammation, apoptosis of olfactory cells, and damage to olfactory neurons and stem cells. Sodagar et al (2022) reviewed the pathological features, neuroinflammatory mechanisms, and potential treatments of SARS-CoV-2 in the brain, finding strong infection of the olfactory bulb, thalamus, and brainstem. Karimian et al (2022) explored the molecular mechanism of SARS-CoV-2-induced olfactory deficit, suggesting that OD may be a temporary or long-term complication caused by olfactory neuroepithelial disorders, with the Delta and Omicron strains relying on TMPRSS2 to enter cells and inducing inflammation, apoptosis, and neuronal damage.…”
Section: Discussion Research Trend Under the Perspective Of Timementioning
confidence: 99%